THE IMPLEMENTATION USING SCIENCE TEACHING AIDS TO INCREASE STUDENTS LEARNING OUTCOME ON D PHASE SOLAR SYSTEM TOPIC ON SMP KARTIKA 1-7 - Eduardo, Kevin; Prima Sari, Monica; Evita Putri, Rahmah (UNIVERSITAS NEGERI MEDAN, 2024)
This study aims to improve the learning outcomes of junior high school students using Science Teaching Aids media on the Topic D Phase Solar System. This research is a classroom action research consisting of 2 cycles. Each cycle that is run consists of the stages of Planning, Acting, Observing, and Reflecting. From the results of research regarding the application of learning media using teaching aids to improve the learning outcomes of students in Phase D Science material on the Solar System using teaching aids. which was held at SMP Kartika 1-7 Padang. This research has the aim that the use of teaching aids in this research can successfully improve students' learning outcomes in science material about the Solar System in class VII. 2 SMP Kartika 1 – 7 Padang. In cycle I, meeting 1, 24% of students achieved a minimum score of 80. In cycle II, meeting 1, the percentage of students who achieved a minimum score of 80 was 36%. Keywords: teaching, aids, solar, system, outcomes.